Distribution of phycotoxins in Última Esperanza Province during the PROFAN expedition 2019. (August 2022) - Möller, Kristof; Pinto-Torres, Marco; Mardones, Jorge I.; Krock, Bernd
Highlights: Marine toxins in the Última Esperanza Province of Magallanes (48.5°-50.5 S) First detection of pinnatoxin-G indicating presence of Vulcanodinium rugosum. Differing PSP toxin profiles among field samples and cultured strains. Abstract: Harmful Algae Blooms pose an increasing threat to the public health and economic stability of Southern Chile, particularly to the aquaculture industries. This fieldwork performed during the PROFAN expedition from 12th to 22nd November 2019 extends the knowledge on the distribution of marine toxin-producing species in the difficult to access Última Esperanza Province in the Magallanes Region. Paralytic Shellfish Poisoning toxins with high relative abundances of saxitoxin and lipophilic toxins dominated by yessotoxins, pectenotoxins and domoic acid were detected at nearly each sampling station. The respective toxin-producing organisms are mainly from the genus Alexandrium and Dinophysis . Furthermore, the first detection of pinnatoxin-G (PnTx-G) in Chilean waters strongly indicates the presence of the dinoflagellate Vulcanodinium rugosum .